Ectopic gallbladder on transverse colon: a rare case report - Phyoe, Swe Z.; Samarasinghe, Priya (International Surgery Journal, 2025)
A woman presented with biliary colic during pregnancy. Her symptoms resolved; however, persistent elevation of gamma-glutamyl transferase (GGT) and progressive increase in gallstone size from 4mm to 18mm over one year was observed on ultrasound. During elective laparoscopic cholecystectomy, the gallbladder was unexpectedly found on the transverse colon, rather than the liver bed, presenting unique diagnostic and surgical challenges.